Benign Mullerian Glandular Inclusions in Men: A Metastatic Carcinoma Mimic. (9th November 2022) - Bhatt, M; Chand, M; Qu, H
Abstract: Introduction/Objective: Benign mullerian glandular inclusions (MGI) in lymph nodes is a well documented finding in women. However, it can also very rarely occur in men and mimic metastatic carcinoma. To our knowledge, only seven cases of benign MGI in men have been reported in the literature. Methods/Case Report: We here-in present a case of a 62-year-old male with a three-year history of prostatic adenocarcinoma Gleason score 6, initially diagnosed on needle core biopsies. Subsequently, the patient underwent a radical prostatectomy with bilateral pelvic lymph node dissection. Histological evaluation of the right pelvic lymph node demonstrated cystically dilated glands beneath the capsule composed of cuboidal to columnar cells with minimal atypia raising concern for metastatic carcinoma to the lymph node. Immunohistochemical (IHC) stains showed the glandular cells to be positive for estrogen, progesterone, PAX-8 and WT-1; while negative for calretinin and PSA immunostains. This IHC profile in conjunction with the morphological findings are consistent with the diagnosis of benign mullerian-type glandular inclusions within the lymph node. Results (if a Case Study enter NA): NA. Conclusion: As benign MGI is a rare finding in men and can easily be mistaken for metastatic carcinoma, this case demonstrates that clinical awareness of this entity is essential to avoid wrongful diagnosis of metastatic carcinoma and unnecessary therapeutic treatment. Utilizing immunohistochemical stains to further characterize the glands is critical to obtain the correct diagnosis.